Analysis of the Advancement of Public-Private Partnership in Ukraine - Negrych, Mykola; Vashkevych, Viktor; Tkachenko, Olena; Kuchmieiev, Oleksandr (Dr. Viktor Koval, 2024)
Introduction. The significant amount of destruction caused by the war in Ukraine necessitates the involvement of all forms of financial and organizational support for the country's reconstruction process. A tried-and-tested method of attracting resources to this process is a public-private partnership. The intensification of public-private partnerships aims to meet the basic needs of the population during martial law before creating the necessary conditions for economic recovery after the war. Since the war led to the stagnation of the specified process, the obstacles and peculiarities of public-private partnerships in this period need to be researched. Aim and tasks. The purpose of this study is to analyse the impact of martial law conditions on the activation of public-private partnerships to reveal its role in the recovery of the country's economy based on the analysis of available data to identify trends and significant results that can shed light on the activation of the public-private partnership process. This determines the following tasks: to investigate obstacles to the activation of public-private partnership from 2021 to this time, and to establish peculiarities, urgent directions, and prerequisites for implementing projects, measures, methods, and forms of public-private partnership in the specified period. Results. The analysis showed that, in recent years, the contractual discipline of partnership projects has significantly deteriorated, and the range of directions for their implementation has narrowed and does not correspond to the priorities specified in the legislation. Thus, in 2021, only 16% of agreements were realized, 16.6% were terminated, and 61.6% still needed to be implemented. Directions for their implementation are not urgent in wartime conditions. Business activity is restrained by the risks of war, incomplete compliance of the legal framework with the conditions of war, and the intensification of illegal actions against investment objects. In total, 363 court cases related to raiding were initiated in 2023, reflecting a two-fold increase compared to 2022. The identified peculiarities, directions, and prerequisites for the implementation of public-private partnerships intensify the implementation process. Conclusions. Measures to reduce risks and change the approaches to their distribution in partnership agreements have been proposed. It is proposed to introduce an institute of small investors, which will strengthen public control of public-private partnership projects and ensure the attraction of additional private investments in the process of rebuilding the country. This is substantiated by the fact that 61% of the surveyed citizens are ready to participate financially in the reconstruction of the country's infrastructure and 33% are ready to participate if they have a financial opportunity.